AKTUALISASI SERAT ZIKIR MAULUD DALAM TRADISI MASYARAKAT Actualisation of Serat Zikir Maulud in Community Traditions - Endah Susilantini (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Serat Maulud Zikir is a work of Islamic literature containing the greatness of God by presenting miracles at the time of the birth of the Prophet Muhammad, until he became an apostle (rasul). In addition, Serat Zikir Maulud also reveals the exemplary of the prophet with elements of faith, morals, and practices and its relevance in the present day. This study tries to reveal the values content in Serat Zikir Maulud and how the birth of the prophet has inspired the living traditions in society. This study is library research by collecting books related to the topic. The findings of research are the content of Serat Maulud Zikir containing a moral message and noble values which benefit for the life of society today. God has planned everything so that the presence of Prophet Muhammad (peace be upon him) in the Jahiliyyah (ignorance) society was actually to remind people to get closer and worship to God. The event of the prophet’s birth was commemorated in various places and called the celebration of Maulud Nabi. In Yogyakarta and Surakarta palace, the birth of Prophet Muhammad (peace be upon him) is commemorated with Sekaten traditional ceremony which is held every year.